Impacts Zero Over Dimension Over Loading Regulatory Compliance, Transportation Renewal Strategy, and Route Optimization On Operational Cost Efficiency - Alya Fadyah wahyudi; Muhammad Tohir (Siber Journal of Transportation and Logistics, 2025)
The effect of Zero Over Dimension Over Loading Regulatory Compliance, Transportation Renewal Strategy, and Route Optimization on Operational Cost Efficiency is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence of variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley, and other academic online media. The research method employed in the research library utilizes e-books and open-access e-journals. The results of this article: 1) Zero Over Dimension Over Loading Regulatory Compliance has an effect on Operational Cost Efficiency; 2) Transportation Renewal Strategy has an effect on Operational Cost Efficiency; and 3) Route Optimization has an effect on Operational Cost Efficiency.